2010
DOI: 10.1074/jbc.m109.078790
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity of Triplet Repeat RNAs

Abstract: Tandem repeats of various trinucleotide motifs are present in the human transcriptome, but the functions of these regular sequences, which likely depend on the structures they form, are still poorly understood. To gain new insight into the structural and functional properties of triplet repeats in RNA, we have performed a biochemical structural analysis of the complete set of triplet repeat transcripts, each composed of a single sequence repeated 17 times. We show that these transcripts fall into four structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
153
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(166 citation statements)
references
References 60 publications
13
153
0
Order By: Relevance
“…Circular Dichroism Shows That the r(GGGGCC) n Repeat Forms a Parallel G-quadruplex-CD spectroscopy is a biophysical means to assess G-quadruplex formation in RNA (28,29). CD analysis of the r(GGGGCC) 4 repeat in potassium buffer revealed a positive peak around 260 nm and a negative peak around 240 nm (Fig.…”
Section: Ion Dependence Of the Slow Migrating R(ggggcc)mentioning
confidence: 99%
“…Circular Dichroism Shows That the r(GGGGCC) n Repeat Forms a Parallel G-quadruplex-CD spectroscopy is a biophysical means to assess G-quadruplex formation in RNA (28,29). CD analysis of the r(GGGGCC) 4 repeat in potassium buffer revealed a positive peak around 260 nm and a negative peak around 240 nm (Fig.…”
Section: Ion Dependence Of the Slow Migrating R(ggggcc)mentioning
confidence: 99%
“…Gene ZFHX3, being a transcription factor, can manifest its function in a variety of ways, and be a cause of different stroke subtypes. The gene contains trinucleotide repeats that can participate in expression of its function (Sobczak et al, 2010). It has been shown that changes in the expression of ZFHX3 gene and other candidate stroke genes correlate with miRNA level variation (Dhiraj et al, 2013;Ji et al, 2016;Liang, Lou, 2016;Qingfeng et al, 2016;Chen et al, 2017).…”
mentioning
confidence: 99%
“…The cleavage patterns of these transcripts determined at 37 ° C do not show any hallmarks of hairpin structures. Finally, as many as seven TNR RNAs, the AAG, CAA, CCA, CCU, CUU, UAA and UUG motifs, appeared unable to form any secondary structures (Sobczak et al , 2010 ). The structural variety of the TNR RNAs may reflect their potential to interact with a variety of RNA binding proteins and perform diverse biological functions.…”
Section: Structural Classes Of Isolated Triplet Repeatsmentioning
confidence: 99%
“…However, this number is reduced to 20 different TNRs when the four homonucleotide motifs are excluded and the three different phases of the 60 individual sequence motifs are combined. Recently, the ability of these TNRs to adopt higher-order RNA structures has been investigated by chemical and enzymatic structure probing and biophysical methods (Sobczak et al , 2010 ). As a result, the TNRs have been divided into four structural classes: (I) very stable G-quadruplex structures, known also as G-quartets; (II) semi-stable hairpins; (III) unstable hairpins; and (IV) not forming any higher order structures (Figure 1 A).…”
Section: Structural Classes Of Isolated Triplet Repeatsmentioning
confidence: 99%